EFEKTIFITAS PEMBELAJARAN DENGAN PENDEKATAN KONTEKSTUALvDAN PENDEKATAN PEMECAHAN MASALAH DITINJAU DARI GAYA BELAJAR PADA SISWA SEKOLAH MENENGAH PERTAMA DI KABUPATEN BOJONEGORO - Abdul Ghofur; Tri Atmojo Kusmayadi; Suyono Suyono (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective in the research is to find out: (1) the learning approach giving better learning achievement, whether learning with contextual approach with problem solving approach or with direct learning; (2) the student learning style providing better learning achievement, whether visual, auditory, or kinesthetic learning styles; (3) in each learning approach, who having learning achievement better, the students with visual, auditory or kinesthetic learning style; and (4) in each learning style, which one providing better learning achievement, the learning with contextual approach with problem solving approach or with direct learning. The population of research was all IX (ninth) graders of Junior High School in Bojonegoro Regency consisting of 55 school. The sample was taken using stratified cluster random sampling. The sample of research consisted 305 students divided into experiment I, experiment II, and control groups.The conclusion of research was: (1) the learning with contextual approach giving better mathematics learning achievement than the problem solving approach and direct learning. (2) The students with visual learning style had learning achievement better than those with auditory one. But, there was no difference of learning achievement between the students with visual and those with kinesthetic learning style and there was no difference of learning achievement between the students with auditory and those with kinesthetic learning style. (3) In learning with contextual approach, all learning styles had the same learning achievement, while in the learning with problem solving approach, the students with visual learning styles had different learning achievement, the students with visual learning style had the same learning achievment with the students with kinestetic learning styleand the students with auditory learning style had the same learning achievment with the students with kinestetic learning style. Indirect learning, there was no difference of learning achievement between the students with visual, auditory and kinesthetic learning styles. (4) In the students with visual,auditory and kinesthetic learning style, there was no difference of learning achievement between the students with contextual approach,problem solving approach and direct learning.Keywords: contextual, problem solving, learning style.